Pengaruh Metode Team Game Tournament (TGT) Dalam Meningkatkan Minat Belajar Siswa Kelas VII di SMP Swasta Nur Adia Medan - Zailani, Zailani; Tawarni, Tawarni (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The purpose of the study was to determine the effect of the Team Games Tournament (TGT) method in increasing student interest in learning at Nur Adia Private Junior High School Medan, especially for class VII, which consisted of 30 students. The type of research used is qualitative research. In this study, the researchers used the principal, tutor teachers and students as resource persons. Observations and interviews were conducted to obtain results about the Team Games Tournament method which aims to increase student interest in learning. This type of cooperative learning model TGT (Team Games Tournamnet) proves that with this method students' interest in learning increases rapidly, 1) students are more active in learning because the teacher promises rewards or awards, 2) students can learn more fun and entertained, 3) foster a sense of mutual respect and responsibility. With this method, it can encourage progress in the quality of education and increase student interest in learning in the world of education.